Characterization of the direct interaction between apple condensed tannins and cholesterol in vitro - Zeng, Xiangquan; Du, Zhenjiao; Ding, Xiaomeng; Jiang, Weibo (Food chemistry, 2020)
•CH quenched the fluorescence of ACT via a static mechanism.•The interaction between ACT and CH was a spontaneous process.•ACT were capable of binding with CH directly in vitro.•ACT were able to precipitate CH mainly via non-covalent bonds.•The characteristics of ACT-CH coprecipitates confirmed the interaction of ACT with CH. To provide the scientific evidences for a possible new hypocholesterolemic mechanism of apple condensed tannins (ACT), the direct interaction of ACT with cholesterol (CH) was investigated in the present study. Our results suggested that the quenching of ACT fluorescence by CH was carried out according to a static mechanism, while the interaction between ACT and CH in vitro was a spontaneous process. ACT were capable of binding with CH directly, and the CH-binding capacity (35.9–43.9%) of ACT remarkably enhanced with the increase of ACT concentration (0.5–2.0 mg proanthocyanidin B2 equivalent/mL). Besides, spectroscopic methods and morphological analysis were used to characterize the ACT-CH coprecipitates, the findings indicated that ACT were able to precipitate CH via ionic interactions, hydrophobic interactions and intermolecular hydrogen bonds rather than covalent bonds. In conclusion, the direct interaction of ACT with CH might play a role in their CH-lowering effects in humans and animals.